2004
DOI: 10.1023/b:sebu.0000029131.67660.ae
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol and Drug Abuse Among Sexual and Nonsexual Offenders: Relationship to Intimacy Deficits and Coping Strategy

Abstract: Three groups of subjects (N = 95) consisting or rapists, child molesters, and a comparison group of violent offenders were examined with reference to history of alcohol abuse, history of drug abuse, intimacy deficits, and emotionally based coping strategies. No differences were found between the two groups of sex offenders on any of the measures examined. Sex offenders were found to be significantly older than the comparison group. When age was entered as a covariate sex offenders were found to have significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
0
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 0 publications
1
14
0
2
Order By: Relevance
“…Empirical studies have shown an increased prevalence of various factors in people with paedophilia and other paraphilias, compared with controls. These include a history of sexual abuse in childhood (Jesperson 2009; Seto 2010; Ogloff 2012), attachment difficulties (Lyn 2004;Marsa 2004;Bogaerts 2005), social incompetence (Dreznick 2003;Seto 2010), emotional dysregulation (Chantry 1994;Ahlmeyer 2003;Seto 2010), and disinhibition caused by empathy deficits (Chaplin 1995;Seto 2010) and substance misuse (Abracen 2000;Looman 2004;Seto 2010).…”
Section: Theories Of Sexual Offending and Paraphiliasmentioning
confidence: 99%
“…Empirical studies have shown an increased prevalence of various factors in people with paedophilia and other paraphilias, compared with controls. These include a history of sexual abuse in childhood (Jesperson 2009; Seto 2010; Ogloff 2012), attachment difficulties (Lyn 2004;Marsa 2004;Bogaerts 2005), social incompetence (Dreznick 2003;Seto 2010), emotional dysregulation (Chantry 1994;Ahlmeyer 2003;Seto 2010), and disinhibition caused by empathy deficits (Chaplin 1995;Seto 2010) and substance misuse (Abracen 2000;Looman 2004;Seto 2010).…”
Section: Theories Of Sexual Offending and Paraphiliasmentioning
confidence: 99%
“…They also noted that a substantial percentage of offenders (28%) were under the influence of alcohol, drugs, or both around the time of commission of the sexual offense (7). Other studies have supported the finding that substance use disorders are common among sexual offenders (8,9).…”
mentioning
confidence: 92%
“…Research so far has taken into account mainly the traditional ways of coping with stress (cf. Shulman and Cauffman 2011 ; Connor-Smith et al 2000 ; Wadsworth and Compas 2002 ; Looman et al 2004 ; Cortoni et al 1999 ), overlooking religious strategies, whose essence lies in reference to religion—or, more accurately, to the sphere of the sacred (Pargament 1997 ). Some religious strategies have a positive character, for example, seeking a way to change one’s life in religion, and these usually involve better adaptation—they reduce the indicators of depression as well as correlate with higher self-esteem, satisfaction with life, and quality of life (Harrison et al 2001 ).…”
Section: Introductionmentioning
confidence: 99%